High-dose-rate brachytherapy for eyelid carcinoma: Implant technique and review - Guinot, Jose Luis; Gutierrez, Cristina; Vercher, Mar; Juárez, Marc; Santos, Miguel Angel; Núñez, Monica; Canos, Sandra; Slocker, Andrea; Najjari, Dina (Journal of Contemporary Brachytherapy, 2025)
Eyelid carcinoma is a tumor often detected at an early stage, which can be managed surgically. In non-surgical cases, brachytherapy is a valid alternative or as adjuvant therapy when risk factors exist. Basal cell carcinoma is the most common type of eyelid cancer, usually occurring in the lower eyelid. Interstitial technique with plastic tubes is a simple procedure in this location. High-dose rate (HDR) brachytherapy offers local control rates greater than 94%, with few side effects and good function preservation. This article provided practical description of the technique and review of literature. Collaboration between ophthalmology, dermatology, and brachytherapy specialists is essential to achieve the best patient outcomes.